Concept Good Education with Adab to Build Islamic Human Resource Development - Rakhmad Agung Hidayatullah; Amir Reza Kusuma; Ahmad Saifulloh; Usmanul Khakim (International Journal of Asian Business and Management, 2023)
This study endeavors  to elaborate on the educational philosophy of Syed Muhammad Naquib al Attas. Al Attas' educational thought, if traced according to his background, it cannot be separated from his attention to the current of secularization of science. As a philosopher, his conception of education begins with his view point on the human beings in terms of being very Islamic. For him, secular Western education gave birth to humans who are uncivilized, savage and brought damage not only to nature but also to humanity itself. Moreover , he sees that the cure for the crisis caused by the secularization of knowledge is through education. Therefore,  it is interesting to discuss the concept as proposed by al Attas to solve this problem